Analisis Kebijakan Penghentian Rekruitmen Guru PNS Tahun 2021 - Mutia Nur Putri, Riska; Kurniawan, Ajeng; Zaky Ardiansyah, Muhammad; Setiawan, Farid (JUPE : Jurnal Pendidikan Mandala, 2023)
The teacher acts as a source of information, guides students in the learning process, and provides valuable experience. Through the education they provide, teachers can help students to develop into competent, creative and broad-minded individuals. The existence of a policy to stop the recruitment of PNS teachers can threaten the availability of qualified teachers. In the PNS teacher recruitment system, being a PNS teacher offers career stability, financial security, and various benefits. However, with the termination of PNS teacher recruitment, opportunities to become PNS teachers have become increasingly limited. In this research, we will discuss the important implications of the 2021 civil servant teacher recruitment dismissal policy on the availability and quality of teachers. The method used is descriptive qualitative method with data collection techniques through literature study. The result of this analysis is that the policy of ending PNS teacher recruitment in 2021 in Indonesia is a complex decision with a significant impact on the education sector. Budget control is one of the main reasons behind this policy, but it is necessary to consider the implications for teacher supply and education quality. Keywords: Teachers, Education, Policy.Guru berperan sebagai sumber informasi, membimbing siswa dalam proses belajar, dan memberikan pengalaman yang berharga. Melalui pendidikan yang mereka berikan, guru dapat membantu siswa untuk berkembang menjadi individu yang kompeten, kreatif, dan berwawasan luas. Adanya kebijakan pemberhentian rekrutmen guru PNS dapat mengancam ketersediaan guru yang berkualitas. Dalam sistem rekrutmen guru PNS, menjadi guru PNS menawarkan stabilitas karir, keamanan finansial, dan berbagai tunjangan. Namun, dengan penghentian rekrutmen guru PNS, peluang untuk menjadi guru PNS menjadi semakin terbatas. Dalam penelitian ini, akan dibahas mengenai pentingnya implikasi dari kebijakan pemberhentian rekrutmen guru PNS 2021 terhadap ketersediaan dan kualitas guru. Metode yang digunakan adalah metode kualitatif deskriptif dengan teknik pengumpulan data melalui studi pustaka. Hasil dari analisis ini adalah kebijakan penghentian rekrutmen guru PNS pada tahun 2021 di Indonesia merupakan keputusan yang kompleks dengan dampak yang signifikan terhadap sektor pendidikan. Pengendalian anggaran menjadi salah satu alasan utama di balik kebijakan ini, tetapi perlu dipertimbangkan implikasinya terhadap ketersediaan guru dan kualitas pendidikan.Kata Kunci: Guru, Pendidikan, Kebijakan